Pengaruh Brand Ambassador dan Kualitas Produk terhadap Keputusan Pembelian Produk Skincare Glad2glow di Kota Bekasi - Adde Salsabila Abbas (Indo Publishing, 2026)
The rapid growth of Indonesia's local skincare industry has intensified brand competition, making brand communication and product quality decisive factors in consumer purchase decisions. This study examines the effect of brand ambassador and product quality on purchase decisions for Glad2Glow skincare products in Bekasi City, with Syifa Hadju as the brand ambassador under study. A quantitative associative-causal approach was employed, involving 100 respondents selected through purposive sampling and analyzed using multiple linear regression with IBM SPSS 27. The results show that brand ambassador has a positive and significant partial effect on purchase decisions (t = 3.640; sig. = 0.000), product quality has a positive and significant partial effect (t = 6.422; sig. = 0.000), and both variables simultaneously affect purchase decisions (F = 66.886; sig. = 0.000) with an Adjusted R Square of 0.571. Product quality, particularly BPOM safety certification, was found to be the more dominant predictor compared to the brand ambassador. These findings suggest that Glad2Glow should maintain consistent product quality while optimizing brand ambassador communication to strengthen consumer purchase decisions in competitive local skincare markets.